2006
DOI: 10.1128/aem.02580-05
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Induced Bactericidal Activity of a Nitrogen-Doped Titanium Photocatalyst against Human Pathogens

Abstract: The antibacterial activity of photocatalytic titanium dioxide (TiO 2 ) substrates is induced primarily by UV light irradiation. Recently, nitrogen-and carbon-doped TiO 2 substrates were shown to exhibit photocatalytic activities under visible-light illumination. Their antibacterial activity, however, remains to be quantified. In this study, we demonstrated that nitrogen-doped TiO 2 substrates have superior visible-light-induced bactericidal activity against Escherichia coli compared to pure TiO 2 and carbon-do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
137
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 199 publications
(141 citation statements)
references
References 44 publications
2
137
1
1
Order By: Relevance
“…Previous studies have suggested that TiO 2 photocatalysis on the surface of microbes may generate extremely active electron holes and ROS that attack the outer layer of the bacterium. 11,37 The oxidation of the outer membrane of bacteria, which contains lipids, peptidoglycans and teichoic acid, might result in subsequent cell death. Therefore, the extent of bacterial killing may be inversely proportional to the thickness and complexity of the cell wall and membrane.…”
Section: Antibacterial Activity By Tio 2 Dosementioning
confidence: 99%
“…Previous studies have suggested that TiO 2 photocatalysis on the surface of microbes may generate extremely active electron holes and ROS that attack the outer layer of the bacterium. 11,37 The oxidation of the outer membrane of bacteria, which contains lipids, peptidoglycans and teichoic acid, might result in subsequent cell death. Therefore, the extent of bacterial killing may be inversely proportional to the thickness and complexity of the cell wall and membrane.…”
Section: Antibacterial Activity By Tio 2 Dosementioning
confidence: 99%
“…14,54,55 Several groups have demonstrated effective bacterial and fungal reduction using N-TiO 2 NPs and films. [56][57][58] In the present work, a repeatable, dose-dependent (0-200 μg/mL) toxicity toward E. coli resulted upon blue light treatment (Figure 8). An approximately 1-log reduction in bacterial population was observed with the highest concentration of particles.…”
mentioning
confidence: 93%
“…n recent years, heterogeneous photocatalytic processes that use semiconductor catalysts have emerged as promising microbial disinfection technologies (1)(2)(3)(4)(5)(6)(7). Among the various photocatalysts being used, titanium dioxide (TiO 2 ) has received the greatest interest and has been extensively studied because of its efficiency and perceived environmental safety.…”
mentioning
confidence: 99%